Potency of Low Tannin Sorghum Bran in Diets on Productive Performance and Meat Quality of Native Chicken - Ahmad Mualif Abdurrahman (Gontor AGROTECH Science Journal, 2020)
Sorghum bran is a by-product of sorghum flour production which can still be used as animal feed. The low palatability is a one of the obstacles in using sorghum bran as native chicken feed. The purpose of this study was to determine the potential use of sorghum bran as feed on the performance and meat quality of native chicken. 180 DOC native chickens were divided into 3 treatments and 6 replications using a completely randomized design for 60 days. The treatments used were different level of sorghum bran usage in the feed, namely; 0% (control), 10% (T1), 20% (T2). The data observed included feed consumption, growth, feed conversion ratio, carcass percentage and meat quality. Giving up to 20% sorghum bran in feed did not significantly affect the feed consumption, growth, feed conversion, carcass percentage, and meat quality of native chicken. Therefore, sorghum bran can be used as an energy source of feed up to 20% and has no negative effect on the performance and quality of local chicken meat